African-American performance and theater history : a critical reader - Elam, Harry Justin; Krasner, David, 1952- (OUP E-Books., 2001)
African American Performance and Theater History is an anthology of critical writings that explores the intersections of race, theater, and performance in America. Assembled by two esteemed scholars in black theater, Harry J. Elam, Jr. and David Krasner, and composed of essays from acknowledged authorities in the field, this anthology is organized into four sections representative of the ways black theater, drama, and performance interact and enact continual social, cultural, and political dialogues. Ranging from a discussion of dramatic performances of Uncle Tom's Cabin to the Black Art Movem.